2008
DOI: 10.1111/j.1420-9101.2008.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Song perception among incipient species as a mechanism for reproductive isolation

Abstract: Many functions in behavioural processes of small passerines are regulated via vocal messages. Song plays an important role in the development of reproductive barriers and thus playback experiments can often be used for investigating the potential for reproductive isolation through behavioural mechanisms. Moltoni’s warbler Sylvia (cantillans) moltonii is characterized by diagnostic vocalizations and a peculiar pattern of distribution, being parapatric and partly sympatric with the nominate Sylvia c. cantillans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…Based on a taxonomic point of view, the splitting of subalpina (cf. Shirihai et al 2001) into a different species (Sylvia subalpina, or S. moltonii), as recently proposed on the basis of song perception (Brambilla et al 2008b) and genetic divergence among breeding populations (Brambilla et al 2008a), is also supported by the diagnosability of the males in our sampling population, in addition to strong differences in vocalisations (Brambilla and Guidali 2005) and specific distribution patterns (Brambilla et al 2006(Brambilla et al , 2008c.…”
Section: Discussionmentioning
confidence: 55%
“…Based on a taxonomic point of view, the splitting of subalpina (cf. Shirihai et al 2001) into a different species (Sylvia subalpina, or S. moltonii), as recently proposed on the basis of song perception (Brambilla et al 2008b) and genetic divergence among breeding populations (Brambilla et al 2008a), is also supported by the diagnosability of the males in our sampling population, in addition to strong differences in vocalisations (Brambilla and Guidali 2005) and specific distribution patterns (Brambilla et al 2006(Brambilla et al , 2008c.…”
Section: Discussionmentioning
confidence: 55%
“…(Gargallo 1994, Shirihai et al 2001, Brambilla et al 2007. Recent studies have shown that the breeding ranges of Moltoni's Warbler and nominate Subalpine Warbler S. c. cantillans overlap at several localities in mainland Italy without evidence for interbreeding (Brambilla et al 2006(Brambilla et al , 2008a. Playback tests conducted within and outside the area of overlap in Italy have demonstrated that the two groups do not respond to each other's songs (Brambilla et al 2008a).…”
Section: Turdus Atrogularis Black-throated Thrushmentioning
confidence: 99%
“…Recent studies have shown that the breeding ranges of Moltoni's Warbler and nominate Subalpine Warbler S. c. cantillans overlap at several localities in mainland Italy without evidence for interbreeding (Brambilla et al 2006(Brambilla et al , 2008a. Playback tests conducted within and outside the area of overlap in Italy have demonstrated that the two groups do not respond to each other's songs (Brambilla et al 2008a). A molecular phylogenetic study indicated that Moltoni's Warbler and Subalpine Warbler form separate clades and failed to find evidence for gene flow, even in areas where the two forms have overlapping breeding ranges (Brambilla et al 2008b).…”
Section: Turdus Atrogularis Black-throated Thrushmentioning
confidence: 99%
“…In our assignment to taxonomic rank, we consider morphological and bioacoustic evidence because species specific songs are often crucial in mate selection and a source of reproductive isolation in birds (Marler 1957, Searcy et al 1981, Payne 1986, Slabbekoorn & Smith 2002, Catchpole & Slater 2003, Brambilla et al 2008. In a setting such as the Lesser Sundas, the emergence of a local dialect in a newly colonised area may lead to bioacoustic divergence, followed by reproductive isolation and potential speciation (Martens 1996, Slabbekoorn & Smith 2002, Seneviratne et al 2012.…”
Section: History and Complexity Of Myzomela Classificationmentioning
confidence: 99%